Sicily and its inhabitants’ resistance to the Fatimid governors (296-335 AH / 908-946 AD) - Al-Dhahibawi, Reem Hadi Marhaj; Janahmadi, Fatemeh (Research Journal in Advanced Humanities, 2026)
Sicily is the largest island in the Mediterranean Sea, and is distinguished by its strategic location, as it represents the gateway from the East to the West. Our study aims to identify its geographical and political status, especially in the era of the Fatimid state.The Fatimids realized the political, strategic and economic importance of Sicily, as their presence in Sicily contributed to maintaining their position in Morocco and Egypt after their entry into it, and extending their control over the Mediterranean Sea. The Fatimid governors contributed to protecting the African coasts from Roman invasions, and it also helped to consolidate their extension in Egypt and the Maghreb countries later, but some Fatimid governors abused its people, because they were military leaders, and did not have political experience in managing state affairs, and as a result, a large number of governors were changed by the Fatimid caliphs due to the revolution of the people of Sicily and their dissatisfaction with their presence.The Fatimid governors were also able to eliminate the revolutions and seditions that took place in Sicily, which gave them military experience in fighting the Byzantines, which in turn helped them overpower their wars against the Umayyads in Andalusia, and the Abbasids in the Levant.